A negative retinoic acid response element in the rat oxytocin promoter restricts transcriptional stimulation by heterologous transactivation domains. - Lipkin, S M (1992)
Retinoic acid receptors are ligand-dependent transcription factors that stimulate gene transcription from promoters containing retinoic acid or thyroid hormone response elements. We describe a high-affinity binding site from the rat oxytocin promoter that mediates negative transcriptional regulation by the retinoic acid receptor. To examine whether strong, constitutive transactivation domains would be capable of stimulating gene transcription when bound to this DNA binding site that normally mediates transcriptional repression, we fused the transactivation domain of the herpes simplex viral protein VP16 to the amino terminus of the retinoic acid receptor and tested the activity of the chimeric protein on the negative retinoic acid response element. This chimeric retinoic acid receptor acted as a strong, constitutive transactivator when bound to promoters containing palindromic thyroid hormone/retinoic acid response elements but surprisingly it still repressed gene transcription when bound to promoters containing the oxytocin-negative retinoic acid response element. These results suggest that a negative DNA binding site itself can inhibit the function of even potent constitutive transactivation domains, and provide evidence that tethering of a constitutive transactivation domain to DNA is insufficient to activate gene transcription.